Membangun Resiliensi Organisasi Melalui Transformasi Manajemen Risiko Digital - Pri SisiliaWindy; Irsyad, Irsyad; Tia Ayu Ningrum (CV. ITTC INDONESIA, 2025)
This study examines how organizational resilience can be strengthened through the transformation of digital risk management. The rapid expansion of digital technologies has introduced new forms of operational, cybersecurity, and data-related risks that require adaptive and integrated responses. The purpose of this research is to analyze the key issues that hinder digital resilience, explore strategic approaches organizations can adopt to manage emerging risks, and identify how digital transformation initiatives contribute to long-term organizational sustainability. Using a qualitative descriptive approach, this study synthesizes findings from recent empirical research, policy documents, and organizational case studies to develop a comprehensive understanding of digital risk practices. The analysis reveals that organizations with proactive digital governance, strong cybersecurity frameworks, and continuous risk-monitoring mechanisms achieve higher resilience in navigating technological disruptions. Results also show that leadership commitment, digital literacy, and cross-functional collaboration significantly influence the successful implementation of digital risk management. This study concludes that transforming risk management into a digitally driven, data-supported system enables organizations to anticipate uncertainties, respond quickly to digital threats, and maintain operational continuity. These findings provide practical insights for institutions seeking to strengthen their resilience in an increasingly digital business environment.